2022
DOI: 10.1021/jacs.2c02695
|View full text |Cite
|
Sign up to set email alerts
|

Transient Host–Guest Complexation To Control Catalytic Activity

Abstract: Signal transduction mechanisms are key to living systems. Cells respond to signals by changing catalytic activity of enzymes. This signal responsive catalysis is crucial in the regulation of (bio)chemical reaction networks (CRNs). Inspired by these networks, we report an artificial signal responsive system that shows signal-induced temporary catalyst activation. We use an unstable signal to temporarily activate an out of equilibrium CRN, generating transient host–guest complexes to control catalytic activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Inspired by the autonomous mechanical actuation of muscle powered by ATP, here, we show our access to soft hydrogel actuators with autonomous self-resetting behaviors powered by a chemical fuel. As shown in Figure b, the actuators have a typical double-layer structure with a responsive layer composed of a simple poly­(acrylic acid) (PAA) hydrogel and an irresponsive layer made of soft poly­(dimethylsiloxane) (PDMS); 1-ethyl-3-(3-dimethylaminopropyl)­carbodiimide (EDC) is used as a chemical fuel, which has been widely used to fuel the formation of carboxylic anhydride. The addition of EDC drives the conversion of carboxylic acid groups in the PAA hydrogel into hydrophobic anhydrides, leading to dehydration and thereby bending of the actuator; meanwhile, the anhydrides undergo spontaneous hydrolysis over time, enabling autonomous recovery of the actuator to the original state once EDC is depleted. The concentration of EDC determines the actuation extent and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the autonomous mechanical actuation of muscle powered by ATP, here, we show our access to soft hydrogel actuators with autonomous self-resetting behaviors powered by a chemical fuel. As shown in Figure b, the actuators have a typical double-layer structure with a responsive layer composed of a simple poly­(acrylic acid) (PAA) hydrogel and an irresponsive layer made of soft poly­(dimethylsiloxane) (PDMS); 1-ethyl-3-(3-dimethylaminopropyl)­carbodiimide (EDC) is used as a chemical fuel, which has been widely used to fuel the formation of carboxylic anhydride. The addition of EDC drives the conversion of carboxylic acid groups in the PAA hydrogel into hydrophobic anhydrides, leading to dehydration and thereby bending of the actuator; meanwhile, the anhydrides undergo spontaneous hydrolysis over time, enabling autonomous recovery of the actuator to the original state once EDC is depleted. The concentration of EDC determines the actuation extent and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CB [7] binding was previously shown to dramatically reduce the hydrolysis rate for ester-containing guest species. [44] This effect is likely to also underlie the prolonged kinetics of dissipation observed in the hydrogel state, as CB [7] binding serves to drive accumulation of the methyl ester species by slowing its hydrolysis and thereby promote hydrogel formation and stability.…”
Section: Methodsmentioning
confidence: 99%
“…However, the system works in organic solvent (CH 2 Cl 2 or toluene). Recently, van der Helm et al 165 reported cucurbit[7]uril (CB[7]) as a supramolecular host to encapsulate aniline (catalyst molecule) in an aqueous environment, which can be released via addition of hydrolytically unstable esters as chemical fuel (Fig. 8d ).…”
Section: Small Molecule-induced Switchable Catalytic Systemsmentioning
confidence: 99%
“… 33 Zn(II)-based catalyst, Pseudo-aqueous solution 140 Presence of CO & Cl − ON, 100% Absence of CO and Cl − OFF, No reaction 34 Cu(II)-based catalyst, HEPES buffer (pH 7.0) 170 Oxidative potential ON, - N.R. Reductive potential OFF, - N.R 35 Hydrolysis of acetal Acid catalysis in ‘nanoflask’, Water-saturated toluene 127 UV light ( λ = 365 nm) ON, ~85% Visible light OFF, ~55% 36 Oxidation Cu(I)-bpy & TEMPO, Aqueous borate buffer (pH 9.5)/acetonitrile (1/1) 143 ssDNA antitrigger sequence ON, - N.R ssDNA trigger sequence OFF, No reaction 37 Aneli system, Water/organic substance 177 No CO 2 ON, >94% CO 2 & magnetic field OFF, No reaction 38 Hydrazone formation Aniline, PBS buffer (pH 7.5) 165 Glycine betaine methyl ester ON, - N.R Ester hydrolysis OFF, - N.R 39 Oxidation of furoic acid PBT, Water 173 CO 2 & light ON, >99% N 2 OFF, No reaction 40 Arylation PBT, Water 173 CO 2 & light, ON, 85% N 2 OFF, No reaction …”
Section: Introductionmentioning
confidence: 99%